PEMANFAATAN MEDIA SOSIAL UNTUK MENGURANGI TINGKAT KECEMASAN IBU HAMIL DI MASA PANDEMI COVID-19 - Rahmawati, Elia Ika; Kartikasari, Ratih Indah; Turlina, Lilin; Sari, Ponco Indah Arista (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
This activity seeks to resolve problems that occur in pregnant women during the Covid-19 pandemic in order to fulfill the right to comfort and health in the psychological aspect, especially at the level of anxiety. The program that will be carried out is to empower pregnant women, namely providing counseling through a network or online. The counseling was carried out using the WhatsApp group social media, with the hope of fostering independence in overcoming the anxiety felt, both their own anxiety and anxiety felt by other pregnant women. The result is that pregnant women participate actively and listen well and there is a decrease in symptoms of anxiety for pregnant women before and after being given counseling using the Whatsapp group as peer health education